KAJIAN YURIDIS TERHADAP JUAL BELI PULAU BERDASARKAN HUKUM POSITIF DI INDONESIA - I Gusti Bagus Agung Kusuma Atmaja; Ni Nyoman Muryatini; Anak Agung Ayu Meitridwiastiti (Jurnal Komunikasi Hukum, 2023)
The issues discussed in this study regarding purchasing islands are reviewed from positive laws in Indonesia. The method of research used in this study is normative-juridical. Normatif juridical research examined a code or rule of law as a system building associated with a legal event. The study was conducted with the intent of providing legal arguments asa basis for determining whether an event was right or wrong and how it should be lawful. Studies have shown that until now in Indonesia's positive laws there is no statute of limitation - an invitation that strictly regulates policy on buying and selling islands in Indonesia. Chapter 33 of the 1945 law stipulated that islands were a national asset for the people of Indonesia. Based on a study of the regulations of the law - invitations in Indonesia, both a foreign investor and a foreign corporation could be granted the rights to business, the rights to building and the rights to use for investment in Indonesia. This asserted that foreign citizens could not own land in Indonesia.